Boron-containing NiO-coated Ni-MOF composite material and preparation method thereof

By adding boric acid during Ni-MOF calcination, a boron-containing NiO@Ni-MOF composite material was prepared, which solved the problems of poor circulation stability of existing electrode materials and high safety hazards of using sodium borohydride, and achieved specific capacitance and cycling performance. promote.

CN119480466APending Publication Date: 2025-02-18ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604330.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials have poor cycling stability, and there are safety risks and high costs when using sodium borohydride.

Method used

By adding boric acid during Ni-MOF calcination, a boron-containing NiO@Ni-MOF composite material was prepared. Combined with the combined action of Ni-MOF and NiO, it forms more oxygen vacancy and a larger specific surface area, which increases the specific capacitance and Cyclic performance.

Benefits of technology

The improvement of specific capacitors and the improvement of cycling performance are achieved without the need for dangerous sodium borohydride, which is cheaper and simple and safe in process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480466A_ABST
    Figure CN119480466A_ABST
Patent Text Reader

Abstract

The invention discloses a boron-containing NiO-coated Ni-MOF composite material and a preparation method thereof.The preparation method comprises the steps that firstly, a nickel source and a terephthalic acid solution are mixed and then subjected to a hydrothermal reaction, and Ni-MOF is obtained; ni-MOF and boric acid are mixed and ground according to a certain mass ratio to obtain a mixture, and the mixture is calcined for multiple times to obtain the boron-containing NiO-coated Ni-MOF composite material; the internal resistance of the prepared material is as low as 0.551 omega, and the material has high ion diffusion rate and ultralow charge transfer resistance; the specific capacitance of the boron-containing NiO-coated Ni-MOF composite material prepared under preferable conditions can reach 1054.6 F.g <-1 > when the current density is 1A. G <-1 >; after 3000 times of charge-discharge cycles, 73% of the initial capacitance of the sample can still be maintained; the preparation method is simple in operation process, low in material cost and good in super-capacitor performance, is used as a super-capacitor electrode material, and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of supercapacitor electrode materials, and in particular relates to a boron-containing NiO@Ni-MOF composite material prepared by adding boric acid and a preparation method thereof. Background technology:

[0002] At present, the well-known energy crisis and air pollution caused by excessive consumption of fossil fuels have directly affected people's daily lives in many ways, especially the choice of transportation. Electric vehicles, powered by lithium-ion batteries or hydrogen fuel cell technology, provide environmentally friendly and sustainable solutions for personal / public transportation, but face problems such as range and charging and discharging time anxiety, as well as many safety and stability issues caused by hydrogen storage and high reactivity. Supercapacitors (SCs) have attracted widespread attention due to their outstanding advantages such as high power density, fast charging time and long service life, and are considered to be a supplement or substitute for electric propulsion systems.

[0003] Metal organic frameworks (MOFs) have been widely studied in various fields due to their unique structure and inherent properties. MOFs have been widely used in the field of energy storage due to their superior properties such as large specific surface area, adjustable pore size, good thermal stability, low density, and ordered crystal structure. Transition metal oxides (TMOs) have high theoretical capacitance, reversible Faradaic reaction, stable chemical structure, and rich storage capacity, and exhibit excellent electrochemical capacitance compared to traditional carbon materials. Therefore, combining MOFs with TMOs structures can significantly improve the pseudocapacitive performance of TMOs by increasing redox reaction centers. Patent CN109559902A reports "A metal organic framework-derived cobalt nickel borosulfide material and its preparation method and application". First, Co-Ni MOF was prepared by coordination of metal ions with organic ligands, and then sodium borohydride solution was added dropwise to the aqueous solution of Co-Ni MOF to prepare Co-Ni MOF-B, and sodium sulfide solution was added dropwise to the aqueous solution of Co-Ni MOF-B to prepare Co-Ni MOF-BS. Patent CN110729132 A reports "a method for synthesizing a metaborate column-supported α-Ni(OH)2 material for supercapacitors". This method first reacts nickel nitrate with terephthalic acid in a mixed solvent of ethylene glycol and N,N-dimethylformamide to obtain a metal organic framework material Ni-MOFs, and then uses Ni-MOFs as a precursor, and sodium borate as an etchant in a mixed system of ethanol and water to perform a high-temperature etching reaction to obtain a metaborate column-supported α-Ni(OH)2 material. The document "Metal-organic framework (MOF)-derived amorphous nickel boride: an electroactive material for electrochemical energy conversion and storage application, Sustainable Energy Fuels, 2021, 5, 1184" reports a single-step redox method, using sodium borohydride to convert crystalline Ni-MOF into amorphous nickel boride, which increases the exposed catalytic active centers and accessible surface area, thereby improving its electrochemical performance.

[0004] As can be seen from the above examples, there are already some methods for preparing nickel boride and boron-containing nickel hydroxide composite materials, but these methods are all obtained by adding sodium borohydride to react and obtain the final product. Sodium borohydride is a dangerous chemical that is easy to make explosives. It will produce a large amount of hydrogen during use, which is very dangerous, and its price is about 120,000 yuan / ton, which is very expensive. In addition, the cycle stability of nickel boride and boron-containing nickel hydroxide electrode materials in the above documents is poor. In general, MOFs materials have the characteristics of high specific capacitance but poor cycle performance. When MOFs are calcined, they will be converted into TMOs, which have better cycle stability, but the specific capacitance will be reduced. The present invention adds boric acid during the calcination of Ni-MOF, so that the final product is not completely converted into TMOs, but forms a boron-containing NiO@Ni-MOF composite material, which is compared with the original Ni-MOF, Its specific capacitance and cycle performance are improved. Studies have shown that if boric acid is not added for calcination, Ni-MOF is calcined under the same conditions, and only NiO can be obtained, and its specific capacitance is very low. This method does not require the use of sodium borohydride as raw material, and the boric acid used is cheaper, about 7,000 yuan per ton. The experimental method is simple and has no safety hazards.

[0005] According to research, there is currently no report on the preparation of boron-containing NiO@Ni-MOF composites by adding boric acid during calcination. Summary of the invention:

[0006] The present invention proposes a method for preparing a boron-containing NiO@Ni-MOF composite material by adding boric acid during MOF calcination; due to the joint action of Ni-MOF and NiO, the final composite material produces more oxygen vacancies and a larger specific surface area, taking into account the characteristics of higher specific capacitance and better cycle performance, and it is found that the product formed by multiple calcinations has higher cycle stability.

[0007] A method for preparing a boron-containing NiO@Ni-MOF composite material in the present invention comprises the following steps:

[0008] (1) Weigh 2-3 mmol of terephthalic acid and dissolve it in 10-15 mL of N,N-dimethylformamide to obtain solution A, weigh 3-4 mmol of nickel source and dissolve it in 20-30 mL of N,N-dimethylformamide to obtain solution B, drop solution B into solution A, stir for 50-60 min, then put the stirred solution into a reaction container, keep the reaction container at 120-130° C. for 20-24 h, and cool to room temperature to obtain Ni-MOF;

[0009] (2) The prepared Ni-MOF and boric acid were mixed and ground in a certain mass ratio, Ni-MOF: boric acid = 10:1 / 5:1 / 3:1 / 1:1, and the mixture was transferred to a quartz boat and heated at 200-400°C at a heating rate of 2°C / min for 2-3 hours. The calcined product was washed with water and ethanol several times and dried at 50-70°C for 12-14 hours to obtain boron-containing NiO@Ni-MOF;

[0010] (4) The dried boron-containing NiO@Ni-MOF was placed in a quartz boat and calcined again at a heating rate of 2°C / min at 400-600°C for 2-3h to obtain multiply calcined boron-containing NiO@Ni-MOF.

[0011] Steps to test electrochemical properties:

[0012] The prepared boron-containing NiO@Ni-MOF composite material was used as the electrode material of the supercapacitor, and 6M KOH was selected as the electrolyte solution to test its capacitance performance. The experiment included: cyclic voltammetry curve (CV), constant current charge-discharge diagram (GCD) and electrochemical impedance spectroscopy (EIS). Hg / HgO electrode was selected as the reference electrode, nickel foam containing NiO@Ni-MOF as the working electrode, and platinum wire electrode as the counter electrode to test the electrochemical performance of the electrode material in the electrochemical workstation.

[0013] The reactant nickel source is one of nickel acetate tetrahydrate, nickel nitrate hexahydrate or nickel chloride hexahydrate;

[0014] The reaction vessel is a 50mL polytetrafluoroethylene high-pressure reactor;

[0015] The electrochemical workstation is a Shanghai Chenhua electrochemical workstation (CHI600E); Description of the drawings:

[0016] Figure 1 This is a scanning electron microscope image (SEM) of the boron-containing NiO@Ni-MOF composite material prepared in Example 1;

[0017] Figure 2 and Figure 3 This is a transmission electron microscopy (TEM) image of the boron-containing NiO@Ni-MOF composite material prepared in Example 1;

[0018] Figure 4 is the X-ray powder diffraction pattern (XRD) of the boron-containing NiO@Ni-MOF composite material prepared in Example 1;

[0019] Figure 5 This is the overall spectrum of the X-ray photoelectron spectroscopy (XPS) of the boron-containing NiO@Ni-MOF composite material prepared in Example 1;

[0020] Figure 6 For samples of Examples 1 to 4, the scanning rate is 10 mV·s -1 Cyclic voltammetry (CV) curves tested at 200 ℃ and 700 ℃;

[0021] Figure 7 Cyclic voltammetry (CV) curves of the sample of Example 1 tested at different scan rates;

[0022] Figure 8 The samples of Examples 1 to 4 were subjected to a current density of 1 A·g -1 Constant current charge and discharge (GCD) curve tested at 200 Hz;

[0023] Fig. 9 The constant current charge and discharge (GCD) curves of the sample in Example 1 tested at different current densities;

[0024] Fig.10 The electrochemical impedance spectroscopy (EIS) diagram of the sample obtained in Example 1;

[0025] Fig.11 This is the rate performance diagram of the sample obtained in Example 1;

[0026] Fig.12 This is the cyclic stability diagram of the sample obtained in Example 1. Specific implementation method:

[0027] The present invention is specifically described below in conjunction with the examples, which include the preferred preparation methods of the present invention, including reagent dosages and reaction conditions. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0028] Example 1: Preparation method of boron-containing NiO@Ni-MOF composite material by adding boric acid and calcining multiple times (preferred method):

[0029] Weigh 2.5 mmol of terephthalic acid and dissolve it in 12.5 mL of N,N-dimethylformamide to obtain solution A, weigh 3.6 mmol of nickel chloride hexahydrate and dissolve it in 25 mL of N,N-dimethylformamide to obtain solution B, drop solution B into solution A and stir for 60 minutes. Then put the stirred solution into a high-pressure reactor, keep the reactor at 120°C for 24 hours, and cool to room temperature to obtain Ni-MOF.

[0030] Ni-MOF and boric acid were mixed and ground at a mass ratio of Ni-MOF: boric acid = 5:1, and the mixture was transferred to a quartz boat and heated at 300°C for 2 hours at a heating rate of 2°C / min. The calcined product was washed with water and ethanol several times and dried at 60°C for 12 hours. The dried sample was placed in a quartz boat and heated at 500°C for 2 hours at a heating rate of 2°C / min, and then calcined again to obtain a boron-containing NiO@Ni-MOF composite material calcined multiple times.

[0031] The morphology of the final product boron-containing NiO@Ni-MOF obtained in Example 1 was characterized by a Japanese S-4800 field emission scanning electron microscope (SEM) and a Japanese JEM-2100 transmission electron microscope (TEM), respectively. The phase of the final product in Example 1 was characterized by a Japanese SmartLab9KW X-ray diffractometer (XRD). The elemental composition of the final product in Example 1 was characterized by a British VG ESCA X-ray photoelectron spectrometer (XPS).

[0032] from Figure 1 It can be seen that after calcination, the Ni-MOF spheres cracked and formed many small particles, but the overall shape was still spherical, retaining the original morphology. Figure 2 and Figure 3 It can be clearly observed in the TEM image that after calcination, many small NiO particles are formed, forming a structure in which Ni-MOF encapsulates NiO. Figure 4 This is the XRD diagram of Example 1, and it can be seen that its composition is NiO (JCPDS No. 47-1049) and Ni-MOF. Figure 5 This is the XPS full scan spectrum of Example 1, indicating that the sample mainly contains Ni, C, O and B elements, wherein the atomic percentage content of B element is 9.94%, and the carbon element signal comes from the result of using carbon element as the standard reference in the test.

[0033] Example 2: Preparation of NiO material without adding boric acid but calcined multiple times:

[0034] Weigh 2.5 mmol of terephthalic acid and dissolve it in 12.5 mL of N,N-dimethylformamide to obtain solution A, weigh 3.6 mmol of nickel chloride hexahydrate and dissolve it in 25 mL of N,N-dimethylformamide to obtain solution B, drop solution B into solution A and stir for 60 minutes. Then put the stirred solution into a high-pressure reactor, keep the reactor at 120°C for 24 hours, and cool to room temperature to obtain Ni-MOF.

[0035] The Ni-MOF was placed in a quartz boat and heated at 300°C for 2 hours at a heating rate of 2°C / min. The calcined product was washed with water and ethanol several times and dried at 60°C for 12 hours. The dried sample was placed in a quartz boat and heated at 500°C for 2 hours at a heating rate of 2°C / min, and then calcined again to obtain a boron-free NiO material.

[0036] Example 3: Preparation method of boron-containing NiO@Ni-MOF composite material with addition of boric acid:

[0037] Weigh 2.5 mmol of terephthalic acid and dissolve it in 12.5 mL of N,N-dimethylformamide to obtain solution A, weigh 3.6 mmol of nickel chloride hexahydrate and dissolve it in 25 mL of N,N-dimethylformamide to obtain solution B, drop solution B into solution A and stir for 60 minutes. Then put the stirred solution into a high-pressure reactor, keep the reactor at 120°C for 24 hours, and cool to room temperature to obtain Ni-MOF.

[0038] Ni-MOF and boric acid were mixed and ground in a mass ratio of Ni-MOF:boric acid = 5:1. The mixture was transferred to a quartz boat and heated at 300°C for 2 h at a heating rate of 2°C / min. The calcined product was washed with water and ethanol several times and dried at 60°C for 12 h to obtain a once-calcined boron-containing NiO@Ni-MOF composite material.

[0039] Example 4: Preparation method of NiO@Ni-MOF composite material without adding boric acid:

[0040] Weigh 2.5 mmol of terephthalic acid and dissolve it in 12.5 mL of N,N-dimethylformamide to obtain solution A, weigh 3.6 mmol of nickel chloride hexahydrate and dissolve it in 25 mL of N,N-dimethylformamide to obtain solution B, drop solution B into solution A and stir for 60 minutes. Then put the stirred solution into a high-pressure reactor, keep the reactor at 120°C for 24 hours, and cool to room temperature to obtain Ni-MOF.

[0041] Ni-MOF was placed in a quartz boat and heated at 300°C for 2 h at a heating rate of 2°C / min. The calcined product was washed with water and ethanol several times and then dried at 60°C for 12 h to obtain a once-calcined, boron-free NiO@Ni-MOF composite material.

[0042] Example 5: Electrochemical property test of the electrode materials prepared in Examples 1 to 4:

[0043] The electrode materials prepared in Examples 1 to 4 were coated on the nickel foam and dried. 6M potassium hydroxide was used as the electrolyte. The nickel foam coated with the sample was clamped with an electrode clamp and connected to an electrochemical workstation to test its electrochemical properties.

[0044] The specific operations are as follows:

[0045] (I) Washing nickel foam: Cut the nickel foam into the actual size of 1 cm × 1 cm for testing and place it in a beaker. Add acetone and deionized water in order to just cover the nickel foam. Place it in an ultrasonic cleaner for ultrasonic cleaning for 15 min. Then add 8% dilute hydrochloric acid for ultrasonic cleaning for 25 min. Then, wash it with deionized water several times until the pH value of the cleaning solution is neutral. Finally, add anhydrous ethanol for ultrasonic cleaning for 30 min. Place the beaker containing the clean nickel foam in a 65°C vacuum drying oven and take it out after 24 hours for use.

[0046] (II) Sample coating: Weigh 8 mg of the electrode material prepared in Examples 1 to 4, 1 mg of acetylene black and 1 mg of polyvinylidene fluoride respectively and put them into a mortar, then add 2 to 3 drops of N-methylpyrrolidone as a solvent, grind into a uniform paste, and coat it on a previously cleaned nickel foam of a size of 1 cm×1 cm; put the nickel foam coated with the sample into a vacuum drying oven at 65°C and dry it for 24 hours, take out the dried nickel foam and press it on a tablet press to ensure that the sample is tightly attached to the nickel foam; subtract the nickel foam without the sample from the nickel foam after the sample is coated, and further calculate the mass of the electrode material actually used for the test.

[0047] (III) Testing of electrochemical properties: The nickel foam coated with electrode material was used as the working electrode, the platinum wire as the counter electrode, and the Hg / HgO electrode as the reference electrode, and they were placed in a 6M potassium hydroxide solution through a three-hole electrode holder. The Shanghai Chenhua electrochemical workstation (CHI600E) was used in the Cyclic Voltammetry mode. Figure 6 The samples of Examples 1 to 4 were subjected to a scan rate of 10 mV·s -1 It can be seen that the CV curve integral area of ​​the sample in Example 1 is the highest, indicating that its energy storage capacity is stronger. Figure 7 The voltage scan rates for the sample in Example 1 were 10, 20, 30, 50, 80, and 100 mV·s in the voltage range of 0 to 0.6 V. -1 The cyclic voltammetry (CV) curves at 200 MHz and 800 MHz show that the shape of the CV curves remains good as the scan speed increases, indicating that the samples have good capacitance performance. Figure 8 In the Chronopotentionmetry mode, the samples of Examples 1 to 4 were tested at a current density of 1 A·g -1 GCD curve when . It can be seen that the sample in Example 1 has the longest discharge time and the highest capacitance. Fig. 9 The samples in Example 1 were subjected to current densities of 1, 2, 3, 5, 10, 15, and 20 A·g -1The constant current charge and discharge diagram (GCD) at the time of the current density of 1A g -1 When the specific capacitance reaches 1054.6F·g -1 ; Fig.10 The electrochemical impedance spectrum (EIS) of the sample in Example 1 was measured in the AC Impedance mode. From the impedance diagram, it can be seen that the curve slope of the prepared product is large, the internal resistance is 0.551Ω, and it has a faster ion diffusion rate and ultra-low charge transfer resistance in the electrochemical process, indicating that it has a higher capacitive behavior. Fig.11 This is the rate performance diagram of the sample in Example 1. When the current density is increased from 1A·g -1 Increase to 20A·g -1 When , the rate performance of the sample in Example 1 is 57%. Fig.12 This is the cycle performance diagram of the sample in Example 1. It can be seen from the figure that after 3000 charge and discharge cycles, the sample can still maintain 73% of its initial capacitance, indicating that the sample in Example 1 has high stability and can still maintain excellent capacity value after long-term cycling.

Claims

1. A method for preparing a boron-containing NiO@Ni-MOF composite material, characterized in that: Dissolve 2-3 mmol terephthalic acid in 10-15 mL N,N-dimethylformamide to obtain solution A. Dissolve 3-4 mmol nickel source in 20-30 mL N,N-dimethylformamide is added to obtain solution B, solution B is dropped into solution A and stirred for 50-60 minutes, the stirred solution is placed in a reaction container, the reaction container is kept at 120-130°C for 20-24 hours, and cooled to room temperature to obtain Ni-MOF; Ni-MOF and boric acid are mixed and ground according to a certain mass ratio, the mixture is transferred to a quartz boat and kept at 200-400°C for 2-3 hours at a heating rate of 2°C / min, the calcined product is washed with water and ethanol for multiple times and then dried at 50-70°C for 12-14 hours to obtain a boron-containing NiO@Ni-MOF composite material; the boron-containing NiO@Ni-MOF composite material is placed in a quartz boat and kept at 400-600°C for 2-3 hours at a heating rate of 2°C / min to obtain a boron-containing NiO@Ni-MOF composite material that has been calcined multiple times.

2. As claimed in claim 1, a method for preparing a boron-containing NiO@Ni-MOF composite material, characterized in that: The reactant nickel source is one of nickel acetate tetrahydrate, nickel nitrate hexahydrate, and nickel chloride hexahydrate; The reaction vessel is a 100 mL polytetrafluoroethylene autoclave; The mass ratio of Ni-MOF to boric acid is Ni-MOF:boric acid=10:1 / 5:1 / 3:1 / 1:

1.

3. As described in claims 1-2, a method for preparing a boron-containing NiO@Ni-MOF composite material, a preferred embodiment, characterized in that: 2.5 mmol of terephthalic acid was weighed and dissolved in 12.5 mL of N,N-dimethylformamide to obtain solution A, 3.6 mmol of nickel chloride hexahydrate was weighed and dissolved in 25 mL of N,N-dimethylformamide to obtain solution B, solution B was dropped into solution A and stirred for 60 min, the stirred solution was placed in a high-pressure reactor, the reactor was kept at 120°C for 24 h, and cooled to room temperature to obtain Ni-MOF; Ni-MOF and boric acid were mixed and ground in a mass ratio of Ni-MOF:boric acid = 5:1, the mixture was transferred to a quartz boat and heated at 300°C for 2 h at a heating rate of 2°C / min, the calcined product was washed with water and ethanol for multiple times and then dried at 60°C for 12 h; the dried sample was placed in a quartz boat and heated at 500°C for 2 h at a heating rate of 2°C / min to obtain a boron-containing NiO@Ni-MOF composite material that was calcined multiple times.

4. As claimed in claim 3, a boron-containing NiO@Ni-MOF composite material, the electrochemical characteristics of which are: at a current density of 1A·g -1 When the specific capacitance reaches 1054.6F·g -1 The internal resistance of the prepared electrode material is 0.551Ω, and after 3000 charge and discharge cycles, it can still maintain 73% of its initial capacitance.

Citation Information

Patent Citations

  • Metal organic framework-derived cobalt-nickel-boron sulfide material as well as preparation method and application thereof

    CN109559902A

  • Application of metaborate column supported alpha-phase nickel hydroxide material supercapacitor

    CN110729132A